Academic health science centre models across the developing countries and lessons for implementation in Indonesia: a scoping review. Issue 9 (6th September 2022) - Bismantara, Haryo; Ahern, Susannah; Teede, Helena J; Liew, Danny
Abstract : Objective: To describe models of academic health science centres (AHSCs) across developing countries, in order to inform AHSC development in Indonesia. Design: Scoping review with systematic methods. Data sources: Ovid MEDLINE, ProQuest Central, Wiley online library, Scopus and Web of Sciences were searched for relevant publications from 1 January 2015 to 1 December 2020. 'Grey literature' was hand searched by targeted website searches, Google searches, as well as personal communication held with stakeholders in Indonesia specifically. Relevant articles regarding AHSCs in developing countries are included. The review would be synthesised to focus on the purpose, structure and core activities of AHSCs. Strategies for success were also considered. Results: Twenty-six recognised AHSCs in developing countries were identified, located in Asia (n=13), Europe (n=1), South America (n=7) and Africa (n=5). Innovation, health system improvement and enhancement in academic capacity were the common visions. Most centres are functionally integrated and university-led. Most AHSCs include community health services to complement primary stakeholders such as academic institutions and hospitals. Limited information was identified regarding patient and public involvement and workforce capacity building. Five AHSCs have been piloted in Indonesia since 2018, integrating universities, academic hospitals and provincial health offices. However, information regarding their core activities and successes is limited. Conclusions: The review suggests that limited published data are available on AHSC models in developing countries, but they still provide important insight into AHSC development in Indonesia. Innovation and health systems strengthening are the common visions. Functional integration with university leadership is the most common model of governance. Other than universities and hospitals, community health centres, research centres and regional health offices are common partners. There is a little description of community engagement and workforce capacity building.